Effect of metallacarborane salt H[COSANE] doping on the performance properties of polybenzimidazole membranes for high temperature PEMFCs. Issue 32 (31st July 2020) - Olvera-Mancilla, Jessica; Escorihuela, Jorge; Alexandrova, Larissa; Andrio, Andreu; García-Bernabé, Abel; del Castillo, Luis Felipe; Compañ, Vicente
Abstract : The preparation and characterization of composite proton exchange membranes containing protonated cobaltacarborane H[Co(C2 B9 H11 )2 ] names as H[COSANE] and different polybenzimidazole (PBI) for a high temperature PEMFC applications is reported. Abstract : In this paper, a series of composite proton exchange membranes comprising a cobaltacarborane protonated H[Co(C2 B9 H11 )2 ] named (H[COSANE]) and polybenzimidazole (PBI) for a high temperature proton exchange membrane fuel cell (PEMFC) is reported, with the aim of enhancing the proton conductivity of PBI membranes doped with phosphoric acid. The effects of the anion [Co(C2 B9 H11 )2 ] concentration in three different polymeric matrices based on the PBI structure, poly(2, 2′-( m -phenylene)-5, 5′-bibenzimidazole) (PBI-1), poly[2, 2′-( p -oxydiphenylene)-5, 5′-bibenzimidazole] (PBI-2) and poly(2, 2′-( p -hexafluoroisopropylidene)-5, 5′-bibenzimidazole) (PBI-3), have been investigated. The conductivity, diffusivity and mobility are greater in the composite membrane poly(2, 2′-( p -hexafluoroisopropylidene)-5, 5′-bibenzimidazole) containing fluorinated groups, reaching a maximum when the amount of H[COSANE] was 15%. In general, all the prepared membranes displayed excellent and tunable properties as conducting materials, with conductivities higher than 0.03 S cm −1 above 140 °C. From an analysis of electrode polarization (EP) the proton diffusion coefficients and mobility have been calculated.